2006
DOI: 10.3892/ijo.28.6.1429
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen enhances the efficacy of an oncolytic HSV-1 mutant in the treatment of estrogen receptor-positive breast cancer

Abstract: Abstract. Oncolytic herpes simplex virus-1 (HSV-1) mutants selectively replicate in and lyse tumor cells. Viral replication is dependent on the cellular proliferative mechanism. Estrogen increases cellular proliferation and decreases apoptosis in estrogen receptor-positive (ER + ) human breast cancer cells. We hypothesize that the cellular changes produced by estrogen may enhance oncolytic viral replication and improve the treatment of ER + breast cancer cells. Estrogen increased proliferation and replication … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 43 publications
(70 reference statements)
0
3
0
Order By: Relevance
“…Interestingly, oestrogen may also be combined with oncolytic viruses. In a study by Stiles et al, the addition of oestrogen to the oncolytic HSV-1 NV1066 enhanced the lytic effect of the virus, with an MCF-7 cell death of 95% and 97% in vitro at MOIs of 0.1 and 0.5, respectively, compared to 53% and 87%, respectively, in the absence of estrogen [67]. This finding may be used to target the more immunotherapy-resistant ER+ breast cancers and is worth potential investigation.…”
Section: Overcoming Breast Cancer-specific Challengesmentioning
confidence: 93%
“…Interestingly, oestrogen may also be combined with oncolytic viruses. In a study by Stiles et al, the addition of oestrogen to the oncolytic HSV-1 NV1066 enhanced the lytic effect of the virus, with an MCF-7 cell death of 95% and 97% in vitro at MOIs of 0.1 and 0.5, respectively, compared to 53% and 87%, respectively, in the absence of estrogen [67]. This finding may be used to target the more immunotherapy-resistant ER+ breast cancers and is worth potential investigation.…”
Section: Overcoming Breast Cancer-specific Challengesmentioning
confidence: 93%
“…Anthracycline resistance and survival following relapse was significantly worse for patients with higher MAPK score. Other researchers have shown that increased expression of p-MAPK was associated with resistance to anti-EGFR agents such as gefitinib, 32 radiation therapy, 20 or the mTOR inhibitor rapamycin. 35 Normanno et al 33 reported that gefitinib and PD98059 produced synergistic antitumor effect and increased apoptosis compared with singleagent treatment.…”
Section: Hsv-1 Kills Tnbc and Downregulates The Mapk Pathway S Gholammentioning
confidence: 99%
“…[9][10][11][12][13][14][15] NV1066 is a geneticallyengineered form of HSV-1, which has shown promise as an oncolytic agent against 4110 cell lines, 10 including multiple cancer types, such as mesothelioma, 16 pancreatic cancers, 17,18 melanoma, 19 and breast cancer. 20 Furthermore, NV1066 replicates selectively in cells resistant to apoptosis, and is a derivative of the oncolytic HSV strain NV1020, which has already demonstrated a favorable safety profile in phase I clinical trials. 12,13,21 NV1066 is specifically designed to exploit cells with increased activation of MAPK signaling.…”
Section: Introductionmentioning
confidence: 99%